ILLOCUTIONARY ACTS IN JOKO WIDODO FACEBOOK FAN PAGE - SAGAWATI, JULISA WIRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: speech act, illocutionary act, Facebook, Joko Widodo Facebook fan pageThis study investigates the illocutionary act in the postings of Joko Widodo in Joko Widodo Facebook fan page during his campaign period. There are 2 problems of study namely (1) What are the types of illocutionary acts used in Joko Widodo Facebook fan page ?; (2) What is the dominant type of illocutionary act in Joko Widodo Facebook fan page ?This study used qualitative research design. The data were taken from Joko Widodo Facebook fan page. Specifically, the data were the postings of the Facebook fan page during his campaign from 5 June 2014 until 5 July 2014. The theory of Searle (1979) was employed to figure out the illocutionary acts in the postings of Joko Widodo Facebook fan page.The results of this study showed that all types of illocutionary act were found, except declaratives. There were 27 sentences containing assertives, 21 sentences containing directives, 15 sentences containing commisives, 22 sentences containing expressives, and 4 sentences containing more than one type of illocutionary act. Based on the analysis, assertives were the most frequently used act, followed by expressives, directives, and commisives.To conclude, Joko Widodo often made assertive sentence to attract attention of Indonesian people by his strong statements and assessments. Therefore, he succeeded to achieve supports from people of Indonesian and become the president of Republic of Indonesia.The writer suggests the next reseacher who wants to conduct the similar research to use another subject and scope. For example, in terms of scope the writer suggests to expand the scope such as figuring the perlocutionary act as well.